SYSTEMIC SCLERODERMA OCCURRING AGAINST THE BACKGROUND OF GASTROINTESTINAL TRACT LESIONS AND ITS CLINICAL AND IMMUNOLOGICAL FEATURES - Kadomtseva Larisa Viktorovna; Polikarpova Natalia Vladimirovna; Mirzakarimova Farida Rustamovna (Galaxy International Interdisciplinary Research Journal, 2023)
Systemic scleroderma (SSD) is a disease characterized by a degenerative-sclerosing process of connective tissue of the skin and internal organs with obliterating lesion of arterioles. The disease is generalized, systemic, and progressive and affects mainly women aged 30 to 40 years [2, p. 348; 4, p. 90]. The prevalence of SSD is not yet amenable to accounting due to the small acquaintance of doctors with it and the difficulties of diagnosis, even for a qualified specialist. However, in recent years there has been a noticeable increase in the diagnosis of this disease. Many erased cases of scleroderma are hidden under other diagnoses (Raynaud’s disease, pneumosclerosis, esophageal disease, etc.) [1, p. 4; 3, p. 251].